MEMBANGUN KARAKTER ANAK DENGAN AL-QURAN - Ulandari; Siti Maryam; Siti Ramadhani; Silvia Azzahra; Edi Hermanto (PT. Hasba Edukasi Mandiri, 2026)
Important aspect Character education shaping children’s personalitics is the modera tra which filled with maral and social challenges. The Qur an, as the guideline of life for Muslint, contains educational values that able to develop childrens character into individuals who noble, disciplined, honest, responsible, and socially caring. This study aims to analyze the role of the in building children' character through the implementation of Islamic valers in daily life The research method used is qualitative approach with library research design by examining various sources such as the Qur'an, hadith, books, and scientific journals relevant to childrra character education. The results of the study show that Qur an-based character education can be implemented through the habituation of warship, the exemplary role of parents and trachers, the cultivation of honesty, patience, exsponsibility, and the strengthening of moral values within family and school environmcats. Our saic values taught from is rarly age are able to shape children into. religious individuals with integrity and good social attitudes. Therefore, the Qur it aut only course of spiritual teachings but also serve strong character and sable morality the main foundation for building a generation with strong character and noble morality.